Forensic Accounting: A Means to Fraud Control in Nigerian Economy - Yakubu, Aminu; Medugu, Amos Raphael; Yakubu, Aminu; Livinus, Ruth; Nidiya, Sani Adamu (IJRDO - Journal of Business Management, 2022)
With an upsurge in financial accounting fraud in the global economy, forensic accounting has become an emerging topic of great importance for academic, research and industries. The objective of the study is to examine forensic accounting as a rout to financial fraud control in Nigeria. Specifically, the study examined if there is significant agreement amongst stakeholders on the effectiveness of forensic accounting in financial fraud control, financial reporting and internal control quality. The survey design was used in the study with a sample size of 45 consisting of accountants, management staffs, practicing auditors and shareholders. The simple random technique was utilized in selecting the sample size, while the binomial test was employed in the data analysis. The findings of the study indicate that there is significant agreement amongst stakeholders on the effectiveness of forensic accounting in fraud control, financial reporting and internal control quality. In line with the above findings, we recommend that the Institute of Chartered Accountants of Nigeria, Association of National Accountants of Nigeria and the National Universities Commission should encourage formalization and specialization in the field of forensic accounting. In addition, the government should stimulate interest in forensic accounting for monitoring and investigation of suspected corruption cases.